2021
DOI: 10.1002/epi4.12551
|View full text |Cite
|
Sign up to set email alerts
|

Experience of perampanel monotherapy beyond initial titration to achieve seizure freedom in patients with focal‐onset seizures with newly diagnosed or currently untreated recurrent epilepsy: A post hoc analysis of the open‐label Study 342 (FREEDOM)

Abstract: Objective: This post hoc analysis evaluated whether continued treatment with perampanel monotherapy beyond initial titration may be appropriate for patients with focal-onset seizures (FOS) with currently untreated epilepsy to achieve seizure freedom with an effective dose. Methods: Study 342 (NCT03201900; FREEDOM) is a single-arm, open-label, Phase III study of perampanel monotherapy. Patients aged ≥12 years with untreated FOS received perampanel 4 mg/d in a 32-week Treatment Phase (6-week Titration and 26-wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 11 publications
(18 reference statements)
3
12
0
1
Order By: Relevance
“…Notably, in this trial, PWE who experienced a seizure when treated with PER 4 mg/ day during a 26-week maintenance period could be uptitrated to 8 mg/day and reassessed in an additional 26-week maintenance period [8]. A post hoc analysis of the trial demonstrated that a third of PWE who experienced seizures during the titration period of the 4 mg phase of the study went on to achieve seizure freedom during the maintenance period at 4 mg/day [27]. This led the authors to conclude that, in clinical practice, it may be inappropriate to discontinue or switch from PER monotherapy based solely on seizure response before an effective dose has been reached, since the half-life of PER is approximately 105 hours and it may take 2-3 weeks before steadystate plasma PER concentrations are attained [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, in this trial, PWE who experienced a seizure when treated with PER 4 mg/ day during a 26-week maintenance period could be uptitrated to 8 mg/day and reassessed in an additional 26-week maintenance period [8]. A post hoc analysis of the trial demonstrated that a third of PWE who experienced seizures during the titration period of the 4 mg phase of the study went on to achieve seizure freedom during the maintenance period at 4 mg/day [27]. This led the authors to conclude that, in clinical practice, it may be inappropriate to discontinue or switch from PER monotherapy based solely on seizure response before an effective dose has been reached, since the half-life of PER is approximately 105 hours and it may take 2-3 weeks before steadystate plasma PER concentrations are attained [27].…”
Section: Discussionmentioning
confidence: 99%
“…A post hoc analysis of the trial demonstrated that a third of PWE who experienced seizures during the titration period of the 4 mg phase of the study went on to achieve seizure freedom during the maintenance period at 4 mg/day [27]. This led the authors to conclude that, in clinical practice, it may be inappropriate to discontinue or switch from PER monotherapy based solely on seizure response before an effective dose has been reached, since the half-life of PER is approximately 105 hours and it may take 2-3 weeks before steadystate plasma PER concentrations are attained [27]. In the current study, PER monotherapy was initiated using slow titration (<2 mg/week) in less than a quarter of PWE (22.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Husni et al [13] performed a post hoc analysis study of 342 PER monotherapy patients with focal onset seizures along with untreated recurrent epilepsy with an effective dose beyond initial titration to achieve seizure freedom. It is a single-arm, open-label, Phase-III study in patients with focal-onset seizures aged over 12 years, 4 mg/day with 30-week treatment phase of 4-week titration period and 26-weeks maintenance period.…”
Section: Open-label Phase-iii Trail Freedom Studiesmentioning
confidence: 99%
“…Ikemoto et al, 2019;Kanemura et al, 2019;Lin et al, 2019;Maschio et al, 2019;Stavropoulos et al, 2019;Takahashi et al, 2019;Abril Jaramillo et al, 2020;Coppola et al, 2020;Kim et al, 2020;Liguori et al, 2020;Maschio et al, 2020;Moraes et al, 2020;Pascarella et al, 2020;Santamarina et al, 2020;Toledano Delgado et al, 2020;Yamamoto et al, 2020;Basheikh and Sadler, 2021;Canas et al, 2021;Davis Jones et al, 2021;Im et al, 2021;Inoue et al, 2021;Labate et al, 2021;Lattanzi et al, 2021;Limotai and Jirasakuldej, 2021; Lossius et al, 2021;Nilo et al, 2021;Rodríguez- Osorio et al, 2021;Sagar et al, 2021;Zhang et al, 2021;Chinvarun, 2022;Husni et al, 2022). A diagram summarizing the process of study selection is shown in Figure1.…”
unclassified